The New Entrepreneurship in Higher Education: The Impact of Tuition Increases at an Ontario University - Quirke, Linda; Davies, Scott (Canadian Journal of Higher Education, 2002)
Recent increases in university tuition fees are part of a new entrepre- neurial trend in higher education in which institutions are expected to generate more of their own revenue. We examine the effects of this trend on access to universities for students of lower socioeconomic origins, and identify a series of cross cutting pressures. On the one hand, tuition fees pose an obvious financial barrier for these students, whom researchers have shown to be relatively cost-sensitive and debt-averse. On the other hand, the demand for university education among youth from all backgrounds remains buoyant, and student cultures may be increasingly resigned to accepting large debts to finance their schooling. We then examine empirical evidence from two surveys from the University of Guelph, along with some supplementary sources. We find that the representation of students from low socioeconomic backgrounds fell substantially during a decade of rising tuition costs. In discussing this finding, we link the phenomena of higher and de-regulated tuition to the new entrepreneurship, and argue that it has the potential to increasingly stratify Canadian higher education.